ChemInform Abstract: Synthetic Studies Toward the Citrinadins: Enantioselective Preparation of an Advanced Spirooxindole Intermediate. Issue 43 (21st October 2014) - Matsumaru, Takanori; McCallum, Monica E.; Enquist, John A.; Smith, Genessa M.; Kong, Ke; Wood, John L.
Abstract A strategy for the enantioselective synthesis of spirooxindole (I), an intermediate suited for conversion to the natural enantiomers of marine‐derived alkaloids citrinadin A and B, is developed.